Pemikiran Ali al-Madini tentang kaidah ‘Ilal al-Hadits (Studi Kitab ‘Ilal al-Hadits wa Ma’rifah al-Rijal wa Tarikh) - Muhammad Tahir Alibe (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Ali al-Madini's thoughts on the rule of 'Ilal al-Hadist (Study of the Book of 'Ilal al-Hadits wa Ma'rifah al-Rijal wa Tarikh)'Ilal al-Hadits is understood as a hadith that appears valid, but in fact is daif. Scholars sometimes find it difficult to detect a hadith that has illat. Even scholars say to detect a hadith that has illat required the power of intuition, memorization, a deep understanding of the hadith. Ali al-Madini became a central figure in laying down the rules of 'ilal al-hadits, his opinion was always a reference by later scholars, however, there were not many special books written on 'ilal al-hadits that studied. This study aims to examine the thoughts of Ali al-Madini about 'ilal al-hadits by referring to his book 'Ilal al-Hadits wa Ma'rifah al-Rijal wa Tarikh. Knowing the hadiths that have illat will be studied in the book. This type of research is qualitative with a philosophical approach. The philosophical approach means that the media is used to carefully analyze Ali al-Madini's thoughts on the 'ilal hadith based on his book. The results of this study indicate that Ali al-Madini in detecting the 'ilal hadith is more focused on the area of hadith sanad. He did not find his explanation of 'ilal al-hadits related to the matan of hadith. This can be a gap of criticism against him for not paying attention to the area of matan hadith. In addition, if the narrator is judged to be jarh, the hadith is considered rejected, if the narrator is judged to be ta'dil, then the history is considered valid. The implication of this research shows that the development of 'ilal al-hadiys still needs to be developed by scholars after the Ali al-Madini generation, however, Ali al-Madini becomes the central figure in determining the rules of 'ilal al-hadits